Recycling manure as cow bedding: potential benefits and risks for UK dairy farms - Lech, Katharine. A.; Archer, Simon C.; Breen, James E.; Green, Martin J.; Ohnstad, Ian C.; Tuer, Sally; Bradley, Andrew J. (Elsevier, 2015)
Material obtained from physical separation of slurry (recycled manure solids; RMS) has been used as bedding for dairy cows in dry climates in the US since the 1970s. Relatively recently, the technical ability to produce drier material has led to adoption of the practice in Europe under different climatic conditions. This review collates the evidence available on benefits and risks of using RMS bedding on dairy farms, with a European context in mind. There was less evidence than expected for anecdotal claims of improved cow comfort. Among animal health risks, only udder health has received appreciable attention. There are some circumstantial reports of difficulties of maintaining udder health on RMS, but no large scale or long term studies of effects on clinical and subclinical mastitis have been published. Existing reports do not give consistent evidence of inevitable problems, nor is there any information on clinical implications for other diseases. The scientific basis for guidelines on management of RMS bedding is limited. Decisions on optimum treatment and management may present conflicts between control of different groups of organisms. There is no information on the influence that such 'recycling' of manure may have on pathogen virulence. The possibility of influence on genetic material conveying antimicrobial resistance is a concern, but little understood. Should UK or other non-US farmers adopt RMS, they are advised to do so with caution, apply the required strategies for risk mitigation, maintain strict hygiene of bed management and milking practices and closely monitor the effects on herd health.